(untitled) (Journal of Social Sciences Review, 2023)
This article meticulously examines the historical, present, and future dimensions of the Kashmir disputes, encompassing key aspects such as historical initiatives, challenges faced, recent developments, and future prospects. It delves into the complexities of political obstacles, regional and global influences, and the profound impact on the Kashmiri people. After scrutinizing attempts post-independence and international involvement, the article confronts major setbacks, emphasizing the role of intransigence in impeding resolutions. The evolving dynamics and current state of the Kashmir dispute are explored, providing a nuanced understanding of the region. Drawing from historical analyses, the article extracts crucial lessons and offers insights into future initiatives, underscoring the significance of international community engagement for bilateral diplomatic efforts. Humanitarian concerns take center stage, emphasizing the necessity to address the grievances and protect the rights of the Kashmiri people. The article concludes by presenting future scenarios, ranging from best to worst-case possibilities, encouraging a holistic understanding of potential outcomes. This comprehensive analysis serves as a valuable resource for policymakers, academics, and stakeholders invested in fostering a peaceful resolution to the enduring Kashmir conflict.